"Influencia de la motivación laboral en el clima organizacional de los trabajadores de Scotiabank - Chiclayo" - Mino Pérez, Edgardo Mauricio (2019)
ABSTRACT In this thesis has been determined the influence of work motivation in the organizational climate of the workers of Scotiabank located in the city of Chiclayo. In order to achieve the stated objective, it was important to first determine the level of work motivation as well as the organizational climate of the collaborators of the banking and financial agencies that are the subject of the present investigation. Two questionnaires were used as measurement instruments in the form of a survey, which was constructed and valid, in the case of the motivational level by Juan Antonio Pérez López and for the measurement of the organizational climate Litwin and Stringer (See annex). The questionnaires were designed based on a Likert scale. The investigation is correlational. The main conclusion reached was that the hypothesis was corroborated, since there is a moderate positive influence between the labor motivation in the organizational climate of the Scotiabank workers in the city of Chiclayo. Likewise, the motivational level is at a medium high level and the organizational climate is moderately adequate for the proper functioning of the bank and financial institution under study. The proposal to improve both the motivational level and the organizational culture is aimed at improving the indicators that are at a medium, low, low and very low level.